锰细菌在加拿大海盆、楚科奇海沉积物中的分布 - 高爱国; 陈皓文 (2008)
用平板法分别在4℃和25℃时对北极加拿大海盆和楚科奇海10个沉积物岩芯中的锰细菌进行培养,并测定了检出率和含量.分析结果表明,4℃与25℃温度下培养的锰细菌含量范围均为(-)～3.3×108个.g-1,锰细菌平均检出率分别为77.78%、86.03%,平均含量分别为5.60×106、7.91×106个.g-1;该结果高于太平洋深海沉积物中的锰细菌含量,比北极阿拉斯加淡水湖湖水中的锰细菌含量高1个数量级,比印度洋海岭CarlsbergRidge区热水区海水样品中的锰细菌含量高3个数量级,证实寒冷北极海同样广布锰细菌.对锰细菌在不同水深、经纬度以及沉积物深度中的分布进行了讨论;结果表明,锰细菌检出率随沉积物深度的增加而增大,含量变化呈现浅层少、下层多之势;纬度分布范围较大,并显出有扩大的趋势.水深对沉积物中锰细菌也有一定影响.尽管锰细菌对温度有较强的适应能力,环境温度的升降对本研究区锰细菌具有双重作用. The distribution of Manganese bacteria(MnB)in 10 sediment cores from the Canada Basin and the Chukchi Sea were analyzed by the methods of MPN and plate culture.The cores were sliced in 1 cm intervals from 0~10 cm and at 2 cm intervals below 10 cm on board as subsamples.Retrievability of MnB cultivated in both 4℃ and 25℃ ranged from non-detectable levels(ND)to 3.3×108 CFU·g-1 of wet sample.The occurrence percentages and average numbers of MnB cultivated at 4℃ and 25℃ were 77.78%,5.60×106 CFU·g-1 wet samples,and 86.03%,7.91×106 CFU·g-1 wet samples,respectively.The contents of MnB in sediment cores were higher than those in sediment from the deep Pacific Ocean or in water from Alaska Lake,similar to the results reported in water from the Carlsberg Ridge in the Indian Ocean.The result showed that a tendency of the MnB content increasing from low latitude to high latitude,or from the shallower continental shelf to deeper basin in the south of 78 N.From the surface to deeper sediment,the content of MnB in sediment changed irregularly,depending on the sedimentary environment.It seems that the variability of MnB content was larger at 25℃ than at 4℃. 国家自然科学基金(No.40576060,40376017,40176017)~